Non-pharmacological treatment of Arterial Hypertension in patients assisted in Primary Care in the city of Imperatriz-MA (Research, Society and Development, 2023)
Introduction: The treatment of arterial hypertension has two aspects, pharmacological and non-pharmacological. Both are not dissociated, and in certain cases, the non-pharmacological treatment can prevent the progression and establishment of the disease when the individual is classified as prehypertensive. Objective: to evaluate adherence, as well as the effectiveness of non-pharmacological treatment in hypertensive and pre-hypertensive patients, in patients treated in primary care, in the city of Imperatriz-MA. Methodology: This is a before-and-after study, with an intervention proposal. We evaluated 679 medical records of patients at the Beira Rio Basic Health Unit in Imperatriz, MA. Of these, 145 were visited and 18 accepted the invitation to participate in the research. The inclusion criteria were: being hypertensive or pre-hypertensive, being between 20 and 70 years old, willing to submit to the questionnaire, collection of anthropometric measurements, vital signs and the attempt to adapt to the intervention measures proposed by the team. A self-designed questionnaire was applied and blood pressure monitoring cards were provided. At the time of the visit for collection, an approach was made to what arterial hypertension was and ways to obtain better control based on changes in lifestyle habits. Results: Adherence to non-pharmacological treatment was extremely low, even in those patients with difficult control of blood pressure values ​​with use of more than one medication and associated comorbidities. Conclusion: Changes in life habits face socioeconomic and cultural factors as a barrier, which undermines one of the pillars of the treatment of Systemic Arterial Hypertension.